Introduction and Criticism of the Book of ‘instruction of Arabic Language with Functional Approach’ - Maryam Jalaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book of ‘instruction of Arabic language by functional approach’ by “Davood Abdeh” is one of the rare and vanguard compilations in the field of Arabic language instruction with the functional approach in Arabic world. Hence, the present study introduces the book in the descriptive-analytic method and criticizes it according to the principles of functional approach. Accordingly, after a short introduction about its bases, positive and negative points of the book are reviewed. Using an eloquent and a simple language, the book is like a base for familiarizing instruction system of Arabian countries with functional approach in language instruction; However, this has caused some deficiencies in different parts of the book, the most important of which is the absence of psychological, linguistic, and social functions in the approach. Furthermore, there is no guideline for functional approach in instruction of some language skills.